CFD Analysis of the Effect of Elbow Radius on Pressure Drop in Multiphase Flow - Quamrul H. Mazumder (Modelling and Simulation in Engineering)
Computational fluid dynamics (CFD) analysis was performed in four different 90 degree elbows with air-water two-phase flows. The inside diameters of the elbows were 6.35 mm and 12.7 mm with radius to diameter ratios () of 1.5 to 3. The pressure drops at two different upstream and downstream locations were investigated using empirical, experimental, and computational methods. The combination of three different air velocities, ranging from 15.24 to 45.72 m/sec, and nine different water velocities, in the range of 0.1–10.0 m/s, was used in this study. CFD analysis was performed using the mixture model and a commercial code, FLUENT. The comparison of CFD predictions with experimental data and empirical model outputs showed good agreement.